Cross-Cultural Adaptation, Validation and Standardization of Ages and Stages Questionnaire (ASQ) in Iranian Children. - Roshanak Vameghi; Firoozeh Sajedi; Adis Kraskian Mojembari; Abbas Habiollahi; Hamid Reza Lornezhad; Bahram Delavar (Tehran University of Medical Sciences, 2013)
To provide the validated and standardized form of the Persian version of the Ages and Stages Questionnaires as an appropriate developmental screening tool for evaluation of Iranian children's development.This was a cross-sectional study. Translation and back-translation, content validity determination, cultural and lingual modifications, pilot study on 100 parents and inter-rater reliability determinations were performed, respectively. The national and final stage was carried out 11000, 4-60 month-old children in selected cities throughout the country in order to determine the validity, standard deviation, reliability, sensitivity, specificity, and mean scores points of the test.The reliability, determined by cronbach's alpha ranged from 0.76 to 0.86 and the inter-rater reliability was 0.93. The validity determined by factor analysis was satisfactory. The mean scores of Iranian children were identified and compared with those of the normative sample as well as with three other populations of children. The developmental status of Iranian children was higher in the communication, problem-solving and personal-social domains, especially under the age of 24 months, after which their developmental status seems to deteriorate, especially in the motor domains.The Persian version of the ASQ has appropriate validity and reliability for screening developmental disorders in Iran.